Assessing the Readability and Quality of Zygomatic Implants—Online Information: An English-Language Infodemiologic Study - Saeidi, Abdullah; Bakkari, Ayman; Bakkari, Aser; Shahadah, Samer; Alassaf, Muath; Qazali, Ahmad; Alzahrani, Shadi; Alolayan, Albraa; Elsayed, Shadia A. (European Journal of General Dentistry, 2025)
Zygomatic implants are necessary approach for severe maxillary atrophy patients, yet online information about them are difficult to understand, hindering patients' ability to make informed decisions. By evaluating these resources, the research aims to identify gaps and recommend ways to improve the accessibility and clarity of online health information.Web sites obtained by using English keywords about “Zygomatic dental implant” on Yahoo, Google, and Bing were included in the present study (August 8, 2024). Web sites were assessed using several tools like: DISCERN, Journal of the American Medical Association (JAMA) benchmarks, and readability assessment indices such as Flesch-Reading-Ease, Flesch-Kincaid-Grad- Level, and Simple-Measure of Gobbledygook scales.Seventy-eight Web site were included where 66 Web sites (84.6%) were related to dental/medical centers, while very few numbers of nonprofit organization Web sites provided information specifically on the zygomatic implant, 2 (2.6%). The highest DISCERN scores were linked to the relevance of content question (4.94 ± 0.24). The currency item of the JAMA benchmark was the most achieved item among Web sites (8 Web sites), most of them met by medical and dental centers, while disclosure was the least achieved item (zero Web sites). Only one Web site was categorized as easy. The overall DISCERN score for the identified websites about zygomatic implants indicated a medium level of quality and the average quality question no. 16 of the included Web sites were 2.72 ± 0.50.This study highlights that while the quality of resources is moderate, their poor readability poses a significant challenge. More reliable and readable Web sites that describe the various maxillofacial treatments of zygomatic implant procedures are needed.
Keywords: zygomatic implant; zygoma fixture; readability; DISCERN; JAMA; Web site